Technological and non-technological trends in fashion eco-innovations - Maria Laura Ferranty Maclennan; Eliane Fernandes Tiago; Cristina Espinheira Costa Pereira (Innovation & Management Review, 2023)
Purpose - The fashion industry is diverse and demands a high amount of resources and labor for its operation. It has powerful tools that can positively impact the environment and society as a whole. In this sense, it becomes necessary for fashion to adopt sustainable strategies quickly. One way would be the adoption of eco-innovations by companies in the sector. The objective of this research is to identify the main eco-innovation initiatives carried out by companies in the fashion sector and to verify what the trend is in the sector in relation to the types of eco-innovation, whether technological or non-technological in nature. Design/methodology/approach - To meet the objective, the sector's sustainability reports are analyzed based on the Global Reporting Initiative (GRI) initiative. The method used to treat the data is content analysis. The authors chose to use the GRI-G4 and GRI-Standards versions of the GRI structure, as they include topics relevant to its stakeholders. The analysis based on these criteria considers 18 reports prepared by four companies (Cia Hering, Grupo Malwee, Dudalina and Lojas Renner). Findings - From the data analysis, it was noticed that eco-innovations of technological trends prevail in Brazilian fashion, in the first place, those of process (24.56%), followed by eco-innovations of product (10.53%). The pressure exerted by internal or external stakeholders will be fueled by the current scenario of sustainable development, positively influencing the adoption of eco-innovation. This characteristic can be attributed to the fashion sector, since technological eco-innovations overlap with non-technological ones in all the years that make up the analysis. Research limitations/implications - As limitations of this research, it is worth mentioning the availability of GRIs in the fashion sector. Even considering it a step forward, noting that larger companies support the adoption of these reports, it is important to highlight that only four companies make up the available database (Cia Hering, Lojas Renner, Dudalina and Malwee). From the adoption of the dissemination of sustainability reports by other organizations, the base could be expanded. Practical implications - From this study, practical questions emerge that can contribute to managers and companies in the Brazilian fashion sector. Initially, the focus on eco-innovations is predominantly related to the technological component, with an emphasis on process eco-innovations. In this sense, business actions seek to resolve the accusations normally attributed to the sector, such as the adoption of unsustainable practices. For example, in cotton production, firms use large amounts of pesticides and water, despite the sector being accused of not taking proper responsibility regarding sustainability related issues. Social implications - Investment in eco-innovations indicates a positive attitude and change resulting from pressure and the need to return the market to society's demands for more sustainable production technologies with less environmental impact. Originality/value - The originality of the study lies in the systematization of a GRI analysis model applied to measure eco-innovations in fashion. Through the applied methodology, it is possible to emphasize that eco-innovations of technological trend prevail in the industry, first in processes and then in product development.
Keywords: 650; Green innovation; GRI fashion Industry; Technological trends